Synthesis and Crystal Structure of 4,4',6,6'-Tetrachloro-2,2'-[(1,4-butylene)dioxybis(nitrilmethylidyne)]diphenol - Wang, Li; Dong, Xiu-Yan; Zhao, Li; Yang, Yu-Hua (Asian Journal of Chemistry, 2013)
The compound 4,4',6,6'-tetrachloro-2,2'-[(1,4-butylene)dioxybis(nitrilmethylidyne)]diphenol with the molecular formula C18H16Cl4N2O4, was synthesized by the reaction of 3,5-dichloro-2-hydroxybenzaldehyde with 1,4-bis(aminooxy)butane in ethanol. The molecule is disposed about a crystallographic centre of symmetry and the molecule adopts an extended conformation where the two phenoldoxime moieties are apart from each other. There are strong O-H···N intramolecular hydrogen bond and weak C-H···O and C-H···Cl intermolecular hydrogen bonds and strong intermolecular p-p stacking interactions (the nearest benzene rings are parallel to that of another molecule, are ca. 2.512(2) Å), stabilizing the two dimensional structures of the present compound.